Financial Policies and Capital Markets in Arab Countries - El-Naggar, Said (International Monetary Fund, 1994)
Recent developments at both the international and national levels - including the globalization of financial markets and the wave of liberalization, deregulation, and privatization- have pushed the issue of financial markets to the forefront of the development agenda. This book, edited by Said El-Naggar, comprises the proceedings of a seminar held in Abu Dhabi in January 1994. It provides a comprehensive analysis of various aspects of capital markets in general and particularly in the Arab countries.